The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1002/cyto.b.20631
|View full text |Cite
|
Sign up to set email alerts
|

CD80 (B7.1) is expressed on both malignant B cells and nonmalignant stromal cells in non‐Hodgkin lymphoma

Abstract: Background: CD80 is a member of the B7 family of immune coregulatory proteins that mediate both immune activation and suppression. CD80 in particular has recently been shown to play an important role in supporting immune suppression through interactions with B7-H1. CD80 has been identified as a therapeutic target in non-Hodgkin lymphoma (NHL) based on limited immunohistochemical studies of CD80 expression. Clinical studies have shown that the anti-CD80 antibody galiximab is safe and clinically efficacious in f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 19 publications
0
12
0
2
Order By: Relevance
“…Full activation of T cells requires binding of the CD28 receptor by CD80 or CD86 on antigen-presenting cells [ 38 ]. It was reported that CD80 is expressed in the majority of human DLBCL cases and is also present on nonmalignant stromal cells [ 39 ]. In contrast, one study revealed that acute lymphoblastic leukemia cells have low expression of costimulatory molecules including CD80 and suggested that this probably contributes to the absence of a host T cell-stimulated immune response [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Full activation of T cells requires binding of the CD28 receptor by CD80 or CD86 on antigen-presenting cells [ 38 ]. It was reported that CD80 is expressed in the majority of human DLBCL cases and is also present on nonmalignant stromal cells [ 39 ]. In contrast, one study revealed that acute lymphoblastic leukemia cells have low expression of costimulatory molecules including CD80 and suggested that this probably contributes to the absence of a host T cell-stimulated immune response [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the high efficacy of PD-1 blockade in Hodgkin lymphoma, CD28 is strongly or moderately expressed on T cells surrounding CD80/CD86hi-expressing Reed-Sternberg cells ( 294 296 ). In contrast, chronic lymphocytic leukemia has no or low levels of CD80/CD86 expression on leukemia cells ( 297 299 ) with immunologic synapse formation defects ( 300 ) and is resistant to pembrolizumab in a clinical trial ( 224 ).…”
Section: Overcoming Resistance To Pd-1/pd-l1 Blockade: Various Combinmentioning
confidence: 99%
“…Based on these observations one may conclude that the relative expression of B7‐1 and B7‐2 by malignant cells dictates the prognosis of hematological malignancies. Immune suppression through the interaction between B7‐1 expressed by malignant cells and nonmalignant cells with PD‐L1 has been shown to promote tumor progression in NHL . In this regard, it is likely that targeting this interaction will restore antitumour responses.…”
Section: B7 Ligands In Cancer and Autoimmunitymentioning
confidence: 99%
“…The interaction between B7‐1 and PD‐L1 in vitro provides an inhibitory signal, depicted by reduced T‐cell activation and cytokine production . Binding of PD‐L1 to B7‐1 provides another level of T‐cell regulation during antitumor responses and graft vs host disease . Interestingly, a few studies have demonstrated that PD‐L1 and B7‐1 can interact in cis on the same cell as a mechanism to block interaction with PD‐1 or CTLA‐4 and corresponding T‐cell inhibition .…”
Section: Introductionmentioning
confidence: 99%